Current Management of Primary Immune Thrombocytopenia. Issue 10 (October 2015) - Provan, Drew; Newland, Adrian
Abstract Primary immune thrombocytopenia is an autoimmune disorder of unknown cause affecting both children and adults. The low peripheral blood platelet count is caused by premature platelet destruction by self-reacting antibodies in addition to an impairment of platelet production. The disease is heterogeneous in its pathophysiology, clinical features and responses to treatment. To date, most of the treatments used have been immune-modulating drugs and these contribute to increased morbidity and mortality in patients. A new class of drugs, the thrombopoietin receptor agonists, has been developed for use in ITP. These have gone through randomised controlled trials in large numbers of patients with ITP. These drugs have high efficacy and are well tolerated. In addition, around 30% of patients receiving these drugs are able to stop them and maintain a safe or normal platelet count. Older treatments such as splenectomy are being used less than before, largely because of the introduction of the thrombopoietin receptor agonists. Currently there are trials underway evaluating novel therapies for ITP that will become available over the next few years once the trials are complete.